A Method of Simultaneous Determination of Astronomical Latitude, Azimuth and Time from Observations of an Unknown Star - Bhattacharji, J. C. (The International Hydrographic Review, 2015)
This paper endeavours to evolve a method of simultaneous determination of astronomical latitude, azimuth and time from the observed vertical angles and differences of recorded times and horizontal angles of an unknown star about an hour before and after the time of elongation, either east or west. The special feature of the method is that it does not require actual identification of the star of observation. The determinations being of an order better than third order precision, the method may have ample applications in both topographic and hydrographic surveys including navigation.